Commuters Versus Residents: The Effects of Living Arrangement and Student Engagement on Academic Performance. (November 2019) - Simpson, Denise Balfour; Burnett, Dana
This study focused on the relationship between living arrangement (residential vs. commuter) and the academic performance (grade point average) of first-year, full time undergraduate students at one public, 4-year university in the Southeast. Additionally, we analyzed five educationally effective practices as described by the National Survey of Student Engagement (NSSE): level of academic challenge active and collaborative learning, student–faculty interaction, enriching educational experiences, and supportive campus environment, to identify possible mediators to the relationship between living arrangement and academic performance. We found commuter students earned higher grade point averages than residential students; however, students in both living environments benefited from participating in high levels of academic challenge. While the results of this study challenged the perception that commuters as a group achieve academically at lower levels than residential students, our findings supported prior literature. Our results suggest the amount of time and energy students invest in the college experience relates to students' academic success, regardless of living arrangement.